Implementation of AI Number Generator and A Using GDLC in Android Games - Mochammad Ilham Study Wartana Ilham; I Kadek Dwi Nuryana (Universitas Negeri Surabaya, 2025)
The rapid development of information technology has brought significant changes in various aspects of life, including cultural preservation through digital media. Traditional Indonesian games such as sack racing and hide-and-seek have experienced a decline in interest among the younger generation due to modernization. This research aims to develop Android-based offline games of sack racing and hide-and-seek with the implementation of artificial intelligence (AI) using the Random Number Generator (RNG) algorithm for sack racing games and the A* pathfinding model algorithm for hide-and-seek games. The development methodology used is Game Development Life Cycle (GDLC) with Unity as the main game engine. The implementation of RNG in the sack racing game serves to produce dynamic and unpredictable NPC behavior, such as variations in jump speed and movement patterns. While the A* algorithm pathfinding model in hide-and-seek game allows the searcher NPC to find the optimal path in searching for hiding players, creating a realistic and challenging gaming experience. This research uses functional, performance, and user experience testing to evaluate the effectiveness of the AI implementation.